AN INVESTIGATION INTO LINGUISTIC FEATURES OF BENEFICIARY IN ENGLISH AND VIETNAMESE (IN THE PERSPECTIVE OF FUNCTIONAL GRAMMAR) - Assoc. Prof. Dr. PHAN VĂN HÒA (Trường Đại học Ngoại ngữ, 2025)
To be exact, the study will focus on syntactic and semantic features of the Beneficiary between two languages, and its functions will be discussed.